2005
DOI: 10.1001/archsurg.140.5.432
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Year Prospective Study of Postinjury Multiple Organ Failure

Abstract: The incidence and severity of postinjury multiple organ failure (MOF) has decreased over the last decade. Design: A prospective 12-year inception cohort study ending December 31, 2003. Setting: Regional academic level I trauma center. Patients: One thousand three hundred forty-four trauma patients at risk for postinjury MOF. Inclusion criteria were aged older than 15 years, admission to the trauma intensive care unit, an Injury Severity Score higher than 15, and survival for more than 48 hours after injury. Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
3
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(160 citation statements)
references
References 43 publications
4
142
3
9
Order By: Relevance
“…However, the overall incidence of MOF in trauma patients is higher than that of ARDS, ranging from 15% to 25%, which is three to five times higher than the ARDS incidence. [106][107][108][109] Assuming that the same ratio applies for the incidence in the transfused patients, an estimate of about 45-75% MOF would follow, with a simple average of 60%. However, the only trauma study retrieved on MOF, 109 which reported the transfusion rate, found this rate to be double (45.8%) that of the ARDS study by Chaiwat et al 105 (21%).…”
Section: Complications Related To Trauma And/or Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall incidence of MOF in trauma patients is higher than that of ARDS, ranging from 15% to 25%, which is three to five times higher than the ARDS incidence. [106][107][108][109] Assuming that the same ratio applies for the incidence in the transfused patients, an estimate of about 45-75% MOF would follow, with a simple average of 60%. However, the only trauma study retrieved on MOF, 109 which reported the transfusion rate, found this rate to be double (45.8%) that of the ARDS study by Chaiwat et al 105 (21%).…”
Section: Complications Related To Trauma And/or Transfusionmentioning
confidence: 99%
“…We estimated the probability of mortality in patients with ARDS from a trial in ARDS patients that reported a mortality rate of 83/385 = 21.6%. 111 We pooled data from two studies 106,107 to estimate the mortality rate in patients with MOF (Table 32): a 12-year prospective study of 339 patients with post-injury MOF, 106 and a prediction modelling study of 104 trauma patients of whom 21 developed MOF. 107 This yielded an overall MOF mortality rate of 26.2%.…”
Section: Mortalitymentioning
confidence: 99%
“…Multiple organ failure remains a significant cause of in-hospital morbidity and mortality following traumatic injury (2,19). Although the underlying cellular events leading to MOF are incompletely understood, impaired mitochondrial function and the depletion of cellular energy stores appear to play a central role (35).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that trauma is the leading cause of death for people younger than 45 years old [3]. For those who survive the initial traumatic insult, the most common cause of death is multiple organ failure (MOF) [6,13]. Although the incidence of MOF has slightly decreased over the last 15 years, MOF-related complications, intensive care unit (ICU) length of stay (LOS), and mortality have remained relatively constant [6,22].…”
Section: Introductionmentioning
confidence: 99%
“…For those who survive the initial traumatic insult, the most common cause of death is multiple organ failure (MOF) [6,13]. Although the incidence of MOF has slightly decreased over the last 15 years, MOF-related complications, intensive care unit (ICU) length of stay (LOS), and mortality have remained relatively constant [6,22]. Mechanical tissue damage, ischemic tissue injury (shock), preexisting host factors (age, comorbidities), and the host response all contribute to the development of MOF [24].…”
Section: Introductionmentioning
confidence: 99%